Influencia de los factores socioemocionales en el aprendizaje de lengua y literatura en los estudiantes de educación general básica media de la escuela Segundo Au-hing Medina. - Jurado Ramos, Sara Nicole (2025)
The research aimed to analyze the influence of socio-emotional factors on the learning of Language and Literature among middle-level Basic General Education students at the “Segundo Au-Hing Medina” School, located in the canton of El Empalme, Guayas Province, based on the assumption that emotions such as motivation, frustration, empathy, and self- confidence directly affect academic performance and the development of communicative competences. The study followed a qualitative approach with a non-experimental, cross- sectional design, involving a population of 380 students and 26 teachers, from which a purposive sample was selected consisting of six students and three Language and Literature teachers. Semi-structured interviews, focus groups, non-participant observation, and field journals were employed, enabling data triangulation and a comprehensive analysis. Findings revealed that self-awareness, self-regulation, and empathy significantly influence participation and academic performance, while motivation and the classroom’s emotional climate were identified as the most impactful factors, and it was observed that negative emotional states such as anxiety and frustration limit attention and task completion, in contrast with intrinsic motivation and teacher support, which strengthen reading comprehension and written production. In conclusion, the study confirmed the need to strengthen teacher training in emotional competences to foster meaningful learning and a positive school climate.